ANALYSIS OF RISK FACTORS AND THE IMPACT OF BULLYING BEHAVIOR ON ADOLESCENTS IN JUNIOR HIGH SCHOOLS IN GRESIK REGENCY - suyanto; Prameswari, Riski Dwi; Wardana, Havy; Indarto, Tomi; Kholifah, Anik Nur (Jurnal Ilmiah Kesehatan, 2025)
Bullying is a serious problem, as it can have a long-term impact on severe psychological problems, such as low self-esteem to deep depression, aggression, and school refusal which can lead to dropping out of school. Adolescence is a transitional phase from children to adults, where this group is more at risk of becoming perpetrators or victims of bullying. The role of the surrounding environment is needed to shape the personality of an adolescent. This study is an analytic descriptive study conducted in Gresik Regency in October - November 2024. The study sample was 150 adolescents and analyzed using the Pearson correlation statistical test to see the relationship between variables. The results showed several factors associated with a history of bullying victims and a history of bullying perpetrators were personality factors (p=0.002), aggressive behavior factors (p=0.005), family factors (p=0.021) and factors from mass media (p=0.000). There are many factors that cause bullying behavior among adolescents. The role of the surrounding environment is needed to shape the personality of a teenager. Effective bullying prevention efforts can be carried out in collaboration with schools, parents, and the community.